Education 4.0: Gaps Research Between School Formation and Technological Development - da Motta Reis, José S. [UNESP]; Ferreira Costa, Ana C. [UNESP]; Espuny, Maximilian [UNESP]; Batista, Weslei J. [UNESP]; Francisco, Fernanda E. [UNESP]; Gonçalves, Gildarcio S.; Tasinaffo, Paulo M.; Vieira Dias, Luiz A.; da Cunha, Adilson M.; de Oliveira, Otávio J. [UNESP] (Springer Nature, 2020)
Industry constantly changes following technological developments and innovation, resulting in changes in productivity, the labor market and education. As a result of this new industrial revolution, developed through digitization and robotics, Education 4.0 tends to combine information available in the real and virtual world. The objective of this paper was to identify research gaps, as well as to make groupings through affinity of themes. The adopted method was a literature review, which served as a basis to identify the gaps of the most relevant publications and their variations indexed in the Scopus database. From the identified gaps, it was possible to compose five groups addressing similar characteristics about Education 4.0.
Keywords: Artificial intelligence; Education 4.0; School formation; Technological development